Modelling Oxygen Permeability Through Top Coat and Thermally Grown Oxide in Dense Yb2Si2O7 Environmental Barrier Coatings - Singh, Sonia (Université d'Ottawa / University of Ottawa, 2021)
Environmental barrier coatings (EBCs) are multi-layered systems used to protect hot section components of advanced gas turbine engines from aggressive environments. The state-of-art EBC system consists of a top coat and a bond coat applied on a ceramic substrate. While Ytterbium disilicate (YbDS) is the most used top coat material, Si or SiC are often preferred for the bond coat. During operation, a continuous influx of oxidants through the top coat often leads to reaction with the bond coat to form an additional silica (SiO2) layer called thermally grown oxide (TGO). The growth kinetics of the TGO significantly affects the durability of EBCs. At a critical TGO thickness, the growth stresses exceed the SiO2-bond coat interface strength, resulting in EBC spallation, exposure of the substrate, and eventual failure of the system. The oxidant permeation is a key determinant of the TGO growth kinetics. Therefore, the main objective of this study is to investigate the oxidant diffusion through the EBC system using physics-based and numerical modelling. The oxygen permeability constants for YbDS top coat and TGO are systematically evaluated and quantified in terms of thermodynamics using defect reactions and the parabolic rate constant (kp), respectively. Dry and wet oxygen conditions as well as different temperatures, partial pressures and top coat modifiers are investigated. The results offer evidence that the oxygen permeability constant for the YbDS top coat is an order of magnitude higher than for the TGO. As such, the TGO hinders the oxidant diffusion stronger, proving to be the diffusion rate controlling layer. Moreover, water vapor strongly increases the oxidant permeation with defect reactions playing a key role. It is suggested that the mass transfer through the top coat is primarily by outward ytterbium ion diffusion and inward oxygen ion movement, with the latter being dominant, particularly in wet environments. The effect of top coat modifiers on oxidant permeation is composition sensitive and seems to be related to their interaction with oxygen ions and their mobility.
Keywords: Oxygen permeability; Thermally grown oxide; Top coat; ytterbium disilicate; Environmental barrier coatings